Study on the effect of carbon black, carbon nanotube on the properties of rubber blend acrylonitrile butadiene rubber (NBR)/polyvinyl chloride (PVC) - Hai, Luong Nhu; Suy, Pham Duy; Ngoan, Nguyen Thi; Thuy, Nguyen Van; Tung, Ngo Trinh; Nguyen, Pham Cong; Thuy Hang, Le Thi; The, Ngo Ke (Vietnam Journal of Chemistry, 2017)
The effects of carbon nanotube (CNT) in combination with carbon black (CB) on the properties of acrylonitrile butadiene rubber (NBR)/polyvinyl chloride (PVC) (70/30) were investigated. The results reveal that the maximal tensile strength of the rubber blend was obtained by the fillers ratio of CB:CNT = 39:1. At this filler ratio, the thermal stability and heat conductivity of the rubber blend were also significantly improved. The analysis of FE-SEM images and DMA diagram indicate that the dispersion of filler as well as the interaction between fillers and rubber matrix was improved by the incorporation of CNT. Keywords. NBR/PVC blends, carbon nanotube (CNT), carbon black (CB), nanocomposites.